Characterization of Aluminium-Silicon (Al-Si) cast alloy refined with Titanium Diboride (TiB2) and Scandium (Sc) / R. Rosmamuhamadani... [et al.] - R., Rosmamuhamadani; R.E, Ibrahim; M.K., Talari; M., Yahaya, Sabrina; S., Sulaiman; M.I.S., Ismail (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2018)
The aluminium-silicon (Al-Si) alloys, based on the Metal Matrix Composites (MMCs) system are widely used in light-weight constructions and transport applications requiring a combination of high strength and ductility. A grain refinement plays a crucial role in improving characteristics and properties of Al-Si alloys. In this investigation, titanium diboride (TiB2) and Scandium (Sc) elements were added to the Al alloys for grain refinement of the alloy. Sc is the most widely used and a very effective element for modifying the morphology of eutectic silicon, while TiB2 was commonly present in the commercial grain refiners used for Al-Si alloys. The TiB2 content was fixed at 6wt.% while 0.2-0.8wt.% Sc contents were chosen in this investigation. The Instron Universal Tensile Strength (UTS) machine and Vickers hardness tester were used to characterize the tensile strength and hardness of Al-Si alloys respectively. Optical microscope and x-ray diffraction (XRD) were used to observe the microstructure and to determine the phase distribution in Al-Si alloy. From the results obtained, increased Sc in Al-Si/TiB2 composite alloys has influenced on the grain refinement and improves the mechanical strength of this composite. At the composition of 0.8 wt.% Sc gave the highest value for hardness and tensile strength. The optical microscope showed that the finer microstructure observed when increased the Sc contents to Al-Si-TiB2 composite alloy. From this investigation that has been done, we can conclude that the addition of modifier and grain refiner, TiB2 and Sc will increase hardness and tensile stress of Al-Si cast alloy.